2013
DOI: 10.1590/s0034-737x2013000100015
|View full text |Cite
|
Sign up to set email alerts
|

Correlación de la productividad de un forraje con las propiedades físicas de un Ultisol en Aquidauana

Abstract: O sistema de produção pecuária e os sistemas de manejo do pasto alteram os atributos físicos do solo, refletindo sobre a produtividade e a composição vegetal. O objetivo deste trabalho foi indicar os atributos do solo com melhores correlações lineares e espaciais para se obter zonas específicas de manejo do solo. Foram analisadas as correlações lineares e espaciais entre a produtividade de matéria seca da forragem de Brachiaria decumbens (Stapf) e de alguns atributos físicos de um Argissolo em duas profundidad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
5
7
0
2
Order By: Relevance
“…In contrast, Lima et al (2010a) found data with low to medium variability. Montanari et al (2013), studying Ultisols under signalgrass pasture, found CV values for gravimetric moisture from 10.9 to 13.8 %, which corroborates our study.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast, Lima et al (2010a) found data with low to medium variability. Montanari et al (2013), studying Ultisols under signalgrass pasture, found CV values for gravimetric moisture from 10.9 to 13.8 %, which corroborates our study.…”
Section: Resultssupporting
confidence: 91%
“…With respect to SPR (Table 1), the mean values at depths were ranked by Arshad et al (1996) as high (SRP1) and very high (SRP2), and were thus in agreement with the values observed by Montanari et al (2013) at the second depth. Since the soil surface layer has intense water loss through evaporation and sand content is high in the assessed soil, low values for gravimetric moisture (GM) were expected and proved to be similar to those found by Montanari et al (2013).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…O Brasil possui 220 milhões de hectares de pastagens, sendo a gramínea predominante a do gênero Brachiaria, com 55% de B. decumbens, que apresenta boa adaptação, principalmente às áreas de Cerrado, bioma no qual a qualidade química do solo é mais deficiente (Montanari et al, 2013). Contudo, com o tempo, nem mesmo essas forrageiras rústi-cas têm conseguido bom desenvolvimento nesses solos, pois o consumo da massa verde pelo animal, a falta de reposição dos nutrientes, a acidificação do solo, a perda da maté-ria orgânica e a compactação do solo diminuem a eficiência das pastagens (Moreira et al, 2005;Pariz et al, 2011).…”
Section: Introductionunclassified